Analysis of an Alanine/Arginine Mixture by Using TLC/FTIR Technique. (28th January 2014) - Liu, Jun; Zhou, Feng-shan; Guo, Ran; Jiang, Ye; Fan, Xiaokun; He, Anqi; Zhai, Yanjun; Weng, Shifu; Yang, Zhanlan; Xu, Yizhuang; Noda, Isao; Wu, Jinguang
Abstract : We applied TLC/FTIR coupled with mapping technique to analyze an alanine/arginine mixture. Narrow band TLC plates prepared by using AgI as a stationary phase were used to separate alanine and arginine. The distribution of alanine and arginine spots was manifested by a 3D chromatogram. Alanine and arginine can be successfully separated by the narrow band TLC plate. In addition, the FTIR spectra of the separated alanine and arginine spots on the narrow band TLC plate are roughly the same as the corresponding reference IR spectra.